Insights on guava wilt and its different control measures. (14th December 2021) - Singh, Gursharan; Singh, Jatinder; Arya, Shailendra Kumar
Abstract: Guava ( Psidium guajava L.) wilt is extremely severe and soil borne disease, i.e. difficult to control once the symptoms appear on the plant foliage. It is mainly caused by the fungi like Fusarium oxysporum f. sp. psidii, Fusarium solani, Gliocladium roseum, Cephlosporium sp., Nalanthamala psidii and Gliocladium roseum . Several biocontrol agents based on live bacteria and their enzymes and bioactive compounds released by various fungi reported as the antagonistic strategies against the wilt-causing organisms. Chemical control of guava wilt is also feasible to some extent but the disease may reoccur more aggressively due to the presence of fungal spores in the soil. On the other hand, some well-accepted physical methods, like removal and burning of whole plant are extreme steps to control the disease which cause major financial loss. This review is critically based on the different control measures of guava wilt that have been used in laboratory studies as well as in the guava fields.